Phylogeny of infraorder Sejina (Acari: Mesostigmata) - Lekveishvili, Mariam; Klompen, Hans (Zootaxa, 2004)
Phylogenetic relationships among the families in the infraorder Sejina and the position of Sejina relative to other infraorders of Mesostigmata are re-examined based on molecular and morphological data. Data sets included DNA sequence data for complete 18S, EF-1 , partial CO1genes, and 69 morphological characters. The two families of Heterozerconina consistently group within Sejina, and we propose to synonymize Heterozerconina with Sejina (Sejina s.l). Microgyniina is not the closest relative of Sejina. Rather, Sejina s.l. most often groups with Gamasina. Uropodellidae and Ichthyostomatogasteridae are sister groups and this lineage forms the sister group to Discozerconidae plus Heterozerconidae. Overall, we recognize 5 families within Sejina: Uropodellidae, Ichthyostomatogasteridae, Sejidae, Discozerconidae, and Heterozerconidae.